The Impact of Applying the Driyarkara Philosophy-Based Andragogical Learning Method on Students' Ability to Write Emergency Nursing Care - Irine Yunila Prastyawati; Edy Syahputra Sihombing; Yuni Kurniawaty; Dan Henry F. Gonzales (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Writing Nursing Care Plans (NCP) forms the primary foundation for ensuring quality in the process and documentation of nursing. The Driyarkara philosophy-based andragogy has emerged as a preferred learning method due to its ability to grant students the freedom to explore their learning needs, encouraging them to become more independent, active, and motivated in their studies. To determine the impact before and after the implementation of the Driyarkara philosophy-based andragogical learning method on students' ability to write Emergency NCP. Method: This study employed a quasi-experimental pre-and post-test design with one group, involving 42 respondents selected through total sampling. The intervention consisted of a pre-test assessment, followed by a three-week Driyarkara philosophy-based andragogical learning intervention, and concluded with a post-test assessment. Instruments used included the Emergency Nursing Care assessment sheet and the Adult Learning Principles Design Elements Questionnaire (ALPDEQ). Data were analyzed using the Wilcoxon Signed Ranks Pairs Test. Results: The respondents had an average age of 22.06±0.734 years, with 73.8% (31 respondents) being female. The average satisfaction with the learning method was 9.17±1.342 (range 0–10), while the average motivation was 9.1±1.185 (range 0–10). The p-value was 0.000 < 0.05, indicating a significant difference before and after the intervention, with 41 respondents showing improvement and 1 respondent showing no improvement. Conclusions: The implementation of this method had a positive impact on students' ability to write Emergency Nursing Care Plans, enhancing active participation, fostering a more holistic understanding, and increasing motivation.